An RDF-based distributed expert system - Prapakorn, Napat; Chittayasothorn, Suphamit (My University, 2009)
An expert system or knowledge-based system comprises of a knowledge base and an inference engine in which their expertise knowledge is represented. The knowledge can be called upon when needed to solve a problem by the inference engine. In a large expert system, the knowledge base can be represented using frames. Hence they are called frame-based expert system or frame-based system. To avoid too many communication traffics during inferences, a distributed expert system, an expert system with an inference engine on its external knowledge base side is presented. It is an expert system which has an RDF external knowledge base for improved flexibility and mobility in knowledge sharing. This research presents a design and implementation of a Frame-based RDF expert system which has a RDF/XML database as its external knowledge base. The external knowledge base uses frame as its knowledge representation stored in RDF/XML format so that it can be placed on the WWW (World Wide Web) which is, ideally, accessible from anywhere. With this capability, an expert system will be enriched with flexibility and mobility in knowledge sharing.
Keywords: Expert system; Frames; Knowledge base; Ontology; RDF; RDF/XML